Press start to play : video games and the imagined realities of the cold war - Koh, Kevin Shao Jie (2018)
Press Start to Play: Video Games and the Imagined Realities of the Cold War is a paper that intends to study popular video games that appeared before and during the Golden Age of Arcade Video Games. This was a time during the Cold War when arcade gaming grew in popularity, signifying an era when video games integrated themselves into popular culture. The game worlds of video games have always been fictional. However, they are also conceived by an imagination of what society can be driven to become. Thus, early video games can be seen as a reflection of imagined futures during the Cold War, a period in history which some have argued was based off an imagined fear, eventually turning into an imagined reality. As such, this paper attempts to prove that popular video games during the late twentieth century contributed to the imagination of Cold War escalation by portraying worlds in a constant state of war. These games highlighted violence, invasions and even nuclear fear, which helped to solidify Cold War fears and imaginations to American youths. Video games in essence, had fed into the notion of the Cold War’s imagined reality.